Digital addiction among elementary school children in rural Southeast Sulawesi: A descriptive cross-sectional study - Nurfadilah H., Siti; Effendy, Devi Savitri (Universitas Islam Negeri Alauddin Makassar, 2025)
Previous studies on digital addiction in children have predominantly focused on urban or digitally advanced regions, leaving a gap in understanding how digital behaviors manifest in rural contexts, especially among elementary-aged children. This study aims to describe the level of digital addiction, including screen time and game addiction, among elementary school children in a rural area of Southeast Sulawesi, Indonesia. A descriptive cross-sectional design was applied involving 50 students from State Elementary School 2 Wakorumba Selatan, selected through proportional random sampling. Data were collected using a screen time questionnaire and the Game Online Addiction Scale, then analyzed univariately using SPSS. The results revealed that 54% of children had daily screen time exceeding three hours and 66% were classified as addicted to games. Notably, digital addiction was more prevalent among children over nine years old and among girls. Despite limited personal gadget ownership, many children still accessed digital content, with a recurring habit of playing games before bedtime. These findings highlight the urgent need for targeted digital literacy programs and parental guidance in rural communities. This study contributes to public health by offering evidence to inform community-based interventions and educational policies aimed at preventing digital addiction and promoting healthy digital behaviors among children